Modelo computacional da dinâmica da cadeia de suprimentos do commodity do café brasileiro - Ferreira, Alexandre José (2017)
The Brazilian coffee industry faces new challenges, which can change the structure of production. The coffee market appears to be a complex dynamic system, with dominant negative feedbacks, as well as response delays, which generate oscillations. The dynamic models proposed in the literature for the coffee market are not practical and are not fully calibrated and realistic, although they suggest that oscillations are endogenous. This paper proposes to generate a mathematical and computational model of the dynamics of the Brazilian coffee commodity to investigate its behavior. Where concepts of dynamic systems theory and statistical, associated with market data and analysis, were used. As a computational tool, the Stella Architect software and its features were employed to model the mathematical equations. The dynamic model developed can estimate tree stocks, production, exports, and gross opening stocks of green coffee, among other variables. The dynamic model can therefore be used as a risk management tool and be adapted to receive other functionalities and data, as well as estimate data for longer horizons and different scenarios, serving governments, cooperatives and producers.